Practical tortoise raising, and other philosophical essays - Blackburn, Simon, 1944- (Oxford : Oxford University Press, 2010)
Simon Blackburn presents a selection of his philosophical essays from 1995 to 2010. He offers engaging and illuminating discussions of a wide range of topics, including moral philosophy, the theory of meaning, pragmatism, and the theory of reason and reasoning.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Philosophy